2007
DOI: 10.1519/r-22236.1
|View full text |Cite
|
Sign up to set email alerts
|

The Muscle Strength and Size Response to Upper Arm, Unilateral Resistance Training Among Adults Who Are Overweight and Obese

Abstract: Overweight and obesity result in musculoskeletal impairments that limit exercise capacity. We examined if the muscle strength and size response to resistance training (RT) differed among 687 young (mean +/- SEM, 24.2 +/- 0.2 years) overweight and obese (OW) compared to normal weight (NW) adults as denoted by the body mass index (BMI). Subjects were 449 NW (22.0 +/- 0.1 kg.m(-2), 23.4 +/- 0.3 years) and 238 OW (29.2 +/- 0.2 kg.m(-2), 25.6 +/- 0.4 years) men (n = 285) and women (n = 402) who underwent 12 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
3
30
0
1
Order By: Relevance
“…It is known that obese patients have higher absolute muscle strength compared to lean subjects, but they have lower relative muscle strength (in terms of total body weight) [19,[39][40][41]. The latter gives the patients an impaired functional capacity, meaning that more strength is necessary to handle their heavier body.…”
Section: Discussion Muscle Strength and Muscle Massmentioning
confidence: 99%
“…It is known that obese patients have higher absolute muscle strength compared to lean subjects, but they have lower relative muscle strength (in terms of total body weight) [19,[39][40][41]. The latter gives the patients an impaired functional capacity, meaning that more strength is necessary to handle their heavier body.…”
Section: Discussion Muscle Strength and Muscle Massmentioning
confidence: 99%
“…For example, young adults with higher BMI and greater SAT surrounding the bicep exhibited an attenuated gain in bicep strength with RT, despite a similar relative increase in muscle size as in those who were normal weight or had less SAT (19,20). A recent study in older adults showed that the quality of knee extensor muscle in response to a combined RT, endurance, and balance training intervention only improved in subjects with low thigh IMAT at baseline (21).…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index 20 kg/m 2 and below was defined as underweight, normal weight was 18.5-24.9 kg/m 2 , overweight was 25-29.9 kg/m2 and obesity was above 30 kg/ m 2 . 7 The normal value of triceps skin fold for normal weight men was 12.0mm (standard deviation: 0.5mm) and for overweight men was 18.2mm (standard deviation: 0.6 mm). The normative mean value for muscle strength was 265 Newton (standard deviation:38) for male.…”
Section: Methodsmentioning
confidence: 92%
“…Homosexual men are considered more susceptible to be infected by HIV because of HIV-1 tropism in large intestine endothelial cells, low condom usage, and high promiscuity which make the odds of being infected by HIV 18.7 times higher compared with those in heteronormative adult population in Asia. 1,[4][5][6][7][8] With the lowest estimation of 2.2% proportion from the total male population, men who have sex with men (MSM) is HIV-transmitting niche that is quite big. 9 In Indonesia, for instance, HIV/AIDS is positive in around 2.1 % MSM in Bandung, 5.6% in Surabaya, and 8.1 % in Jakarta.…”
mentioning
confidence: 99%